Structure of the numerical range of a Friedrichs model: 1D case with rank two perturbation - Расулов, Тулкин (Центр Научных Публикаций (buxdu.uz), 2021)
The paper considers a limited and self-contained joint Friedrichs model and a 1-dimensional point analysis in which color is excited by two.